Interactions between childhood maltreatment and brain-derived neurotrophic factor and serotonin transporter polymorphisms on depression symptoms. Issue 1 (30th September 2015) - Harkness, Kate L.; Strauss, John; Michael Bagby, R.; Stewart, Jeremy G.; Larocque, Cherie; Mazurka, Raegan; Ravindran, Arun; Wynne-Edwards, Katherine E.; Rector, Neil A.; Kennedy, James
Abstract: This study represents the first replication of the BDNF Val66Met ⁎ 5-HTTLPR ⁎ childhood maltreatment effect on self-reported depression symptoms using a rigorous maltreatment interview. Participants included a community sample of 339 adolescents/young adults (age 12–33; 265 female). In the context of childhood neglect, among BDNF Met-carriers, s-allele carriers of 5-HTTLPR reported significantly higher depression than l/l homozygotes, whereas a differential relation of 5-HTTLPR genotype to depression was not seen among BDNF Val/Val homozygotes. Highlights: Replication of BDNF Val66Met x 5HTTLPR x child maltreatment relation in depression. Further specification of maltreatment: emotional vs. physical vs. sexual abuse. 339 depressed and non-depressed adolescents; contextual maltreatment interview. 3-way interaction was specific to emotional neglect. Neglect raises risk to depression given genetic diatheses to high stress reactivity.